Aquaculture and biotechnology - Karunasagar, Iddaya (ed.); Karunasagar, Indrani (ed.); and Reilly, Alan (ed.) (Science Publishers, 1999)
Machine generated contents note: 1. Application of Antibody Probes in the Diagnosis and Control of Fish Diseases -- Alexandra Adams -- 2. Listeria monocytogenes-A New Microbiological Hazard in Seafood? -- R.S. Fuchs -- 3. Vaccines and Immunostimulants for Sustainable Aquaculture -- Indrani Karunasagar and Iddya Karunasagar -- 4. Traditional Fermented Fish Products of South East and Far East Asia -- P. Rattagool, Indrani Karunasagar and P. Tauro -- 5. Applications of Molecular Methods for Seafood Quality Control -- Iddya Karunasagar and Indrani Karunasagar -- 6. Applications of Jellyfish Green Fluorescent Proteins -- I. Karunasagar, Andreas Bubert and Werner Goebel -- 7. Recent Developments in Marine Biotechnology -- Indrani Karunasagar and Iddya Karunasagar -- 8. Changing Concepts and Problems in Fishery Development -- T.V.R. Pillay -- 9. Antibacterial Chemotherapy and Drug Resistance in Aquaculture -- Valerie Inglis -- 10. Sex Determination and Differentiation in Teleosts -- T.J. Pandian.